2006
DOI: 10.1049/ip-smt:20060092
|View full text |Cite
|
Sign up to set email alerts
|

Characterising beadless air lines as reference artefacts for S-parameter measurements at RF and microwave frequencies

Abstract: Beadless coaxial air dielectric transmission lines can be used as fundamental reference devices for S-parameter measurements at RF and microwave frequencies. However, for these lines to be used for such applications, they must first be characterised accurately in terms of their impedance and propagation characteristics. This includes assessment of the small amount of loss in the line and the associated impact of this loss on other characteristics. A simple method is presented whereby the loss is determined exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Achieving such tight tolerances is an area of active research and we are identifying promising techniques. For instance, the current uncertainty levels could be reduced by incorporating measurements of custom reflection standards, such as well characterized air-dielectric coaxial lines, into the VNA calibration process (Eiø et al 2006;Wübbeler et al 2009;Roberts & Martens 2014).…”
Section: Reduction Of Systematicsmentioning
confidence: 99%
“…Achieving such tight tolerances is an area of active research and we are identifying promising techniques. For instance, the current uncertainty levels could be reduced by incorporating measurements of custom reflection standards, such as well characterized air-dielectric coaxial lines, into the VNA calibration process (Eiø et al 2006;Wübbeler et al 2009;Roberts & Martens 2014).…”
Section: Reduction Of Systematicsmentioning
confidence: 99%
“…In practice, a line will never be perfectly matched. However, from experience [8], it has been found that equation ( 2) can be used satisfactorily for air lines having |S 11 | and |S 22 | less than 0.01 (linear units) at all frequencies. It has been shown in [9] that, to a first-order approximation at high frequencies, the resistivity, ρ, of a line is related to α as follows:…”
Section: Methods 1: Resistivity From S-parametersmentioning
confidence: 99%
“…However, at higher frequencies these parameters can no longer accurately define these standards. Therefore, at higher frequencies the dimensional properties of the conductors are instead used to calculate the electrical characteristics of the standards [6].…”
Section: Dimensional Metrologymentioning
confidence: 99%